Local Effects of Nest-Boxes for Avian Predators over Common Vole Abundance during a Mid-Density Outbreak - Daniel Jareño; Alfonso Paz Luna; Javier Viñuela (Life, 2023)
At the end of the 20th century, the common vole (Microtus arvalis) colonized the practical totality of agricultural ecosystems in the northern sub-plateau of the Iberian Peninsula. To prevent crop damage, chemical control campaigns using anticoagulant rodenticides have been employed. This approach has a high environmental impact, and it has been banned in most countries in the European Union, including Spain. It is therefore essential to analyze alternative methods with lower environmental impacts. Here we explored the efficacy of biological control by avian predators to reduce vole abundance by providing nest-boxes in croplands. We used an indirect index based on the presence/absence of vole activity signs to measure the effect of nest-boxes on common vole abundance. We found that vole abundance was significantly lower near occupied nest-boxes at distances less than 180 m, where vole abundance increases progressively with increasing distance to the nearest nest-box. We also observed that the predatory pressure negatively affects the vole abundance at the end of the breeding period, considering the total number of fledglings. However, the effect of nest-boxes was highly variable depending on the study area and more limited in alfalfa fields, the optimal habitat for voles in agrarian ecosystems. Thus, nest-box supplementation would be a feasible measure for the biological control of the common vole in Mediterranean ecosystems, but it needs improvements for vole control in alfalfa fields within an integrated pest control program. We provide several recommendations to improve the performance of biological control in alfalfa fields.